IMMUNOENZYMATIC AND ELECTROCARDIOGRAPHIC FINDINGS IN PATIENTS WITH DECOMPENSATED HEART FAILURE SECONDARY TO PRIOR ACUTE MYOCARDIAL INFARCTION BEFORE AND AFTER TREATMENT - Levandovska, Kh. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Chronic heart failure (HF) remains a potentially dangerous fatal stage of any cardiovascular disease demonstrating a steady increase in the prevalence among the general population that is accompanied by a progressive increase in the health care costs for improving the patients’ health or clinical status, increasing their quality of life, reducing the risk of death. There is wide interest in studying biomarkers in HF as they can improve the diagnosis, predict the occurrence of its decompensation, as well as help in assessing treatment effects. The objective of the study was to assess the value of determining the plasma concentration of NT-proBNP and ST2 in the patients with decompensated HF and prior acute myocardial infarction (MI) after treatment with succinic acid and arginine preparations under electrocardiographic control. Materials and methods. There were examined 120 patients with Q-QS wave and non-Q wave MI, stage II A-B decompensated chronic HF according to the classification proposed by Vasylenko V.Kh. and Strazhesko M.D., the NYHA functional class (FC) III-IV. The patients with Q-QS wave MI (60 individuals) were divided into 4 groups depending on the treatment method. The patients with non-Q wave MI (60 individuals) were divided into 4 analogous groups. Study groups were homogenous by age, gender, disease severity, duration of the post-infarction period, clinical signs of decompensation, that served as a basis for inclusion of patients in the study. Results. There was analyzed the dynamics of changes in ECG indicators in the patients with decompensated HF and prior MI under the influence of therapy. At the beginning of controlled treatment, most patients developed signs of left ventricular hypertrophy (LVH) and reduced bioelectrical activity. Therapy applied helped reduce the incidence of sinus tachycardia cases. The studied preparations were shown to have the positive effect on the dynamics of heart rhythm disorders in the patients with decompensated HF and prior Q wave MI. During treatment of the patients with prior non-Q wave MI, the positive dynamics in ECG findings, namely reduction in cardiac bioelectrical activity and LHV, was observed. Myocardial bioelectrical activity had a clear tendency to reduce 1 month, and especially 2 months, after treatment. When analyzing the dynamics of changes in blood levels of NT-proBNP, there was observed its significant reduction in all the groups of the patients after the end of treatment. According to the data presented in Table 1, all the treatment schemes proposed led to a significant reduction in serum levels of this peptide after treatment ended. Conclusions. Thus, we can conclude that the treatment of patients with decompensated HF secondary to prior Q-QS wave or non-Q wave MI with succinic acid and arginine preparations possessing anti-ischemic, antianginal, anti-hypoxic, angioprotective effects, allows providing adequate treatment of decompensated HF, as evidenced by the positive dynamics of changes in immunoenzymatic and electrocardiographic findings. Therefore, we plan to develop an algorithm for assessing the quality of therapy, as well as to determine the frequency and time periods of using these peptides for making therapeutic decisions.